Implementation of Travelling Field Generator in Wind Turbine Applications - Bobby George Joseph (Advanced Aspects of Engineering Research Vol. 13, 2021)
Electrical generators are the starting point of a power system network, they produce electrical energy sufficient enough to feed the consumers. Almost all the generators used for this purpose are AC generators, by also using windmills we extract energy from the wind. A dual rotor wind turbine, according to the present invention includes a rotatable drive shaft, a first rotor assembly connected to the drive shaft, a second independently-rotating rotor assembly coupled to the drive shaft rearward of the first rotor assembly. This type of generators has a very large frictional and rotational losses, the vibrations produced in the tower will also be very high due to two rotating parts. The maintenance cost will also be high. This paper mainly concentrates on the reduction of the losses produced in the dual rotor generator without sacrificing its advantages. In other words, here we are making the generator a single rotor type and we are simulating the second rotor rotation by means of a series of electromagnet and power electronic switches which are switched in a particular manner. Dual rotor wind turbine is now being implemented in various country’s to achieve a greater relative velocity even in the midst of low wind velocity, TFG is such a kind of generator which is motivated from the dual rotor wind turbine.